The Impact of Creative Thinking Application on Employees' Performance at Paramilitary Organization - Theeb, Saed Dirar Mohammad (South Asian Journal of Social Sciences and Humanities, 2025)
This study investigates the impact of applying creative thinking on employee performance  within paramilitary organizations. In particular, civilian police institutions have demonstrated  growing interest in integrating creative thinking as a means to enhance operational efficiency.  These organizations have adopted structured policies and decision-making frameworks  aligned with innovation-driven training strategies to keep pace with rapid scientific and  technological advancements. Effective employee performance in such environments  necessitates a foundation of knowledge, coupled with soft and creative skills, within a  competency-based training system. A quantitative methodology was employed to assess the  influence of creative thinking application on employee outcomes in paramilitary settings. The  study focused on a sample of 120 officers from the Palestinian Civil Police. Structural  Equation Modeling (SEM) was utilized through the Amos software to analyze the  relationship between the key variables. Findings indicate a significant positive effect of  creative thinking application on employee performance. This suggests that performance  enhancement in paramilitary contexts is closely tied to knowledge acquisition and creative  capability development. To maintain service quality and sustain a competitive edge,  organizations must assess employee competencies through scientifically grounded standards  focused on functional efficiency and innovation.
Keywords: Creative Thinking Application; Employee Performance; Paramilitary Organizations